Inequalities of Human Opportunities in India: A State-level Analysis. Issue 2 (August 2018) - Vani, B. P.; Madheswaran, S.
This article attempts to measure the equality of opportunity among children in India at state level based on two waves (2004–2005 and 2011–2012) of data from Indian Human Development Survey. The measurement of access to basic services adjusted for differences associated with circumstances and commonly known as the Human Opportunity Index (HOI) is used following the World Bank methodology. This article also adopts multidimensional framework and modifies the HOI to account for access to multiple services to individuals and thus terms it as Multidimensional Human Opportunity Index (MHOI). The change in the MHOI between the two periods, 2004–2005 and 20011–2012, has been decomposed into scale effect and distribution effect. The findings show that the opportunities to access services are quite low and inequitable at all-India level, except in access to safe drinking water. Over the period of seven years, there is an increase in MHOI and much of it is due to the scale effect and not so much due to the distribution effect. Among the circumstance variables, location of residence and per capita expenditure were found to be crucial in influencing equitable access to basic services. Most of the BIMARU states had low and inequitable access to opportunities. Further, the location of residence (rural/urban) was an important factor in influencing access to services at the state level, with low levels of access in rural areas compared to urban areas. In the light of empirical findings, policy options are suggested.